Distorted agricultural prices cause hunger and resources dilapidation - Pinheiro, António C. (2010)
The main objective of this paper is to present facts and arguments trying to prove that price distortion has been the main reason for the dilapidation of human and physical resources all over the world. In some countries, farmers sell their products at prices below their real cost. In these countries, most often, family labour and equipment depreciation are not accounted as real costs. The expected increase in world population will demand for levels of production much higher than those that are been produced. So, if we want to feed the world in a sustainable way, maintaining the production potential of human and natural resources, a new set of trade and rural development policies have to be implemented across the world, based on regional common markets. To promote these policies, regional organisations (that include several countries) and a new international trade organisation must be created.